(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In this article highlights of the division of the amirates into groups before Tug‘luq Temur Khan’s campaign to Movarounnahr and the beginning of Amir Husayn’s political activity (analysis of sources).